Palladium-Catalyzed Synthesis of Isoquinolinones via Sequential Cyclization and N–O Bond Cleavage of N-Methoxy-o-alkynylbenzamides - Jithunsa, Manita; Ueda, Masafumi; Aoi, Naoki; Sugita, Shoichi; Miyoshi, Tetsuya; Miyata, Okiko (Synlett, 2013)
A palladium-catalyzed controlled 6-endo-dig cyclization process has been developed for the chemoselective synthesis of isoquinolin-1-ones from N-alkoxy-o-alkynylbenzamides. The mechanism and scope of the reaction have also been investigated. Deuterium-labeling studies were used to confirm the intramolecular 1,5-hydrogen shift as a key step in the transformation.
Keywords: alkynes; regioselectivity; palladium; cyclization; amides